The Roles of Attitude in The Storyline of Beauty and The Beast (2017) Movie (Systemic Functional Linguistics Approach) - Arjanti, Alhinsa Oktaviani (Universitas Sebelas Maret, 2021)
This research is about analyzing the attitude used by the script writer in Beauty and The Beast (2017) movie. It is aimed to find the roles of attitude in giving the characterizations in the movie and the roles of attitude in building the narrative text in the movie using systemic functional linguistics approach. This research is a descriptive qualitative research, implementing descriptive comparative method with discourse analysis. The source of the data is the utterances from the characters. Primary data were also collected applied genre relation, characterization theory and systemic functional linguistics, especially appraisal theory. In analyzing the data applied Miles & Hubberman’ s (1992) interactive model with Spradley’s (1980) ethnographic steps which include domain, taxonomy, componential, and cultural context analysis. The results of this research show the findings: (1) attitude takes roles in giving direct and indirect characterizations in the form of physical description, action, emotional and physical reaction, thought, speech, (2) In building the narrative text, affect takes roles to express the characters’ emotional feeling, judgement is used to describe and evaluate the characters’ behavior, and appreciation is used to describe the character’s physical appearance, the setting of place of the story and to give an abstract valuation.